2021
DOI: 10.1002/app.50696
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced wear resistance of ultra‐high molecular weight polyethylene fibers by modified‐graphite oxide

Abstract: A simple and feasible method to enhance the wear resistance of ultra-high molecular weight polyethylene (UHMWPE) fibers was reported. The graphite oxide (GO) prepared using improved Hummer's method was surface modified with hexadecylamine to improve its compatibility with UHMWPE. Combined with well-dispersion of modified-GO (m-GO) in dichloromethane and the fact that the viscosity of UHMWPE suspension can be decreased by dichloromethane, the well dispersed m-GO/dichloromethane was added into UHMWPE suspension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…A lot of investigation indicated that the addition of filler increases the crystallization temperature of polymers, attributed to the heterogeneous nucleation of filler [13,14,42,43]. The interfacial interaction between filler and polymer makes nucleation easier, therefore polymer crystalized at a higher temperature.…”
Section: Crystallization and Meltingmentioning
confidence: 99%
See 1 more Smart Citation
“…A lot of investigation indicated that the addition of filler increases the crystallization temperature of polymers, attributed to the heterogeneous nucleation of filler [13,14,42,43]. The interfacial interaction between filler and polymer makes nucleation easier, therefore polymer crystalized at a higher temperature.…”
Section: Crystallization and Meltingmentioning
confidence: 99%
“…In order to improve the properties of UHMWPE, UHMWPE composites filled by carbon fibers (CF) [5][6][7][8][9][10][11][12][13], carbon nanotube (CNT) [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], and graphene oxide (GO) [33][34][35][36][37][38][39][40][41][42][43] were reported. Despite the excellent performance of these nanocomposites, the high cost of these fillers restricted the widely use of the UHMWPE composites.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] UHMWPE fibers are of great importance to mankind because of their increasing demand in fields ranging from civil materials to basic materials for military aviation depending on their simple structure, low density, outstanding tensile property, excellent wear resistance and other properties. [4][5][6][7][8] The methods for preparing UHMWPE fibers mainly include solid-phase extrusion method, 9,10 surface crystal growth method, 11 plasticized melt-spinning method 12,13 and gelspinning-hot-drawing method 14,15 and so forth. But compared with other preparation methods, the gel-spinninghot-drawing method has many merits, such as excellent properties of prepared fibers, easy control of spinning process and so on.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] It is easier for nanofillers to combine with UHMWPE and exhibit better wear-resistance. [8][9][10] In fact, the tribological properties of UHMWPE matrix had been improved by the nanofillers such as CuO, graphene oxide, TiO 2 and illite-smectite interstratified clay (ISIC) at very low content. [8][9][10][11][12] The ISIC powders have the dual properties of montmorillonite and illite.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] In fact, the tribological properties of UHMWPE matrix had been improved by the nanofillers such as CuO, graphene oxide, TiO 2 and illite-smectite interstratified clay (ISIC) at very low content. [8][9][10][11][12] The ISIC powders have the dual properties of montmorillonite and illite. [13] It can be used in the fields of composites, selfhealing materials, and adsorption materials.…”
Section: Introductionmentioning
confidence: 99%